Pearl Harbor : - Wohlstetter, Roberta (Stanford University Press, 1962)
The book offers a unique analysis of the attack, and doesn't pull any punches. Human failures are analyzed, as well as bureaucratic failures, which were many. The reader comes away with a better understanding of the attitudes prevelant among intelligence authorities of the time, as well as an insight into their workings.